2012
DOI: 10.1016/j.indcrop.2011.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of citric acid and water on thermoplastic wheat flour/poly(lactic acid) blends. I: Thermal, mechanical and morphological properties

Abstract: . Influence of citric acid and water on thermoplastic wheat flour/poly(lactic acid) blends. I: Thermal, mechanical and morphological properties. Industrial Crops and Products, Elsevier, 2012, vol. 37, pp. 238-246 Wheat flour was plasticized with glycerol and compounded with poly(lactic acid) in a one-step twinscrew extrusion process in the presence of citric acid with or without extra water. The influence of these additives on process parameters and thermal, mechanical and morphological properties of injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 26 publications
6
46
1
10
Order By: Relevance
“…The lower storage modulus of the PLA/TPS sheets plasticized with adipate or citrate ester compared to the control formulation indicated a decrease in the rigidity, as observed previously in the mechanical properties ( Table 1). The slight increase in the storage modulus at temperatures of 80-120°C was related to PLA cold-crystallization, as described in other studies [12,13,41], explaining the residual crystallinity observed in the diffractograms. When plasticizers were incorporated into the PLA/TPS matrix, the peak intensity shifted to a lower temperature, and a slight increase in the loss modulus was observed.…”
Section: X-ray Diffractionsupporting
confidence: 81%
“…The lower storage modulus of the PLA/TPS sheets plasticized with adipate or citrate ester compared to the control formulation indicated a decrease in the rigidity, as observed previously in the mechanical properties ( Table 1). The slight increase in the storage modulus at temperatures of 80-120°C was related to PLA cold-crystallization, as described in other studies [12,13,41], explaining the residual crystallinity observed in the diffractograms. When plasticizers were incorporated into the PLA/TPS matrix, the peak intensity shifted to a lower temperature, and a slight increase in the loss modulus was observed.…”
Section: X-ray Diffractionsupporting
confidence: 81%
“…É possível que a concentração do mesmo tenha sido excessiva e que tenha atuado como plastificante como relatado em outros estudos (ABDILLAHI et al, 2013;CHABRAT et al, 2012;SHIRAI et al, 2016). De acordo com Wang et al (2010), o excesso de ácido também pode causar hidrólise das cadeias de amido e PLA comprometendo significativamente as propriedades mecânicas da blenda.…”
Section: Resultsunclassified
“…Diferentes estratégias de compatibilização encontram-se descritas na literatura, sendo a utilização de ácidos carboxílicos, como o ácido cítrico, uma delas (ABDILLAHI et al, 2013;WANG et al, 2010;CHABRAT et al, 2012). Em alguns estudos, a incorporação de ácido cítrico melhorou a interação entre as fases poliméricas do ATP e PLA por reação intercruzada (esterificação e ligação de hidrogênio), produzindo materiais com melhores propriedades mecânicas e de barreira ao vapor de água TEIXEIRA et al, 2012;WANG et al, 2010).…”
Section: Introductionunclassified
“…Schematic representation of a twin-screw extruder consisting of a bilobed barrel and two screws (case of the twin-screw extruder used as a liquid/solid extractor and separator). Colas et al, 2013aColas et al, , 2013b, (v) the extraction of polyphenolic extracts with antioxidant activity (Celhay et al, 2014), (vi) the enzymatic degradation of plant cell walls for the production of second generation bioethanol (Vandenbossche et al, , 2015(Vandenbossche et al, , 2016, (vii) the defibring of lignocellulosic materials for the production of paper pulp (Manolas et al, 1995;Maréchal and Rigal, 1999) and fiberboards (Markessini et al, 1997), (viii) the production of composite agromaterials with proteins (Leyris et al, 1998) or polysaccharides Peyrat et al, 2000;Rouilly, 2002;Jorda, 2003) used as the matrix, (ix) the production of thermoplastic agromaterials by compounding cereals and biobased and biodegradable polyesters (Chabrat et al, 2012;Abdillahi et al, 2013), and (x) the production of injectable biocomposites by compounding a biobased and biodegradable polyester, here used as a matrix, and vegetable fillers (Gamon et al, 2013).…”
Section: The Potential Of Twin-screw Processes For the Fractionation mentioning
confidence: 99%